2005
DOI: 10.1002/chin.200515176
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase Inhibiting Withanolides from Withania somnifera.

Abstract: Steroids U 0300 Cholinesterase Inhibiting Withanolides from Withania somnifera. -Two new compounds, (I) and (II), together with four known compounds, are isolated from the title plants' roots. Compound (II) is reported to show inhibitory potential against butyrylcholinesterase. -(CHOUDHARY*, M. I.; YOUSUF, S.; NAWAZ, S. A.; AHMED, S.; ATTA-UR-RAHMAN; Chem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…One of the most common variations in the withaferin A substitution pattern is the hydrolytic cleavage of the 5,6-epoxide according to the F€ urst-Plattner rule (16), to give the trans-diaxial 5a,6b-diol as in coagulin H (7) and coagulin S (8) isolated from W. coagulans (17,18). A less common cleavage is that occurring in a transdiequatorial manner, as found in 9 and 10 (14), later reported as new by Kuroyanagi et al (19), and in 4-deoxywithaperuvin (11) (20). Compound 12 represents an unusual variant of the above, with a 3a,6a-epoxy bridge (21), which could derive from the cyclization of 10 also present in the same extract.…”
Section: B6b-epoxywithanolides and Related Compoundsmentioning
confidence: 97%
See 1 more Smart Citation
“…One of the most common variations in the withaferin A substitution pattern is the hydrolytic cleavage of the 5,6-epoxide according to the F€ urst-Plattner rule (16), to give the trans-diaxial 5a,6b-diol as in coagulin H (7) and coagulin S (8) isolated from W. coagulans (17,18). A less common cleavage is that occurring in a transdiequatorial manner, as found in 9 and 10 (14), later reported as new by Kuroyanagi et al (19), and in 4-deoxywithaperuvin (11) (20). Compound 12 represents an unusual variant of the above, with a 3a,6a-epoxy bridge (21), which could derive from the cyclization of 10 also present in the same extract.…”
Section: B6b-epoxywithanolides and Related Compoundsmentioning
confidence: 97%
“…Acetylcholinesterase (AChE) inhibitors activate central cholinergic function by increasing the acetylcholine levels in the brain. Bracteosins A (206), B (207), and C (208), isolated from Ajuga bracteosa (108), and withanolide A (504) and withaferin A (1) from W. somnifera, were moderate inhibitors of AChE and BChE (butyrylcholinesterase) (11). Molecular docking studies indicated that all compounds are imbedded in the aromatic gorge of AChE.…”
Section: Cholinesterase Inhibitionmentioning
confidence: 99%
“…We had expected a broader profile of cognitive benefits with WSE due to its diverse pharmacologic actions [22][23][24][25][26][30][31][32][33] ; however, narrower results were obtained in this study. Recent work has indicated that WSE reversed deficits in spatial learning and working memory tasks in mouse models of Alzheimer's disease 43 probably by promoting hepatic clearance of β-amyloid.…”
Section: Discussionmentioning
confidence: 71%
“…[31][32][33] Given these diverse pharmacologic actions, we postulated that adjunctive WSE treatment would improve cognitive functions broadly in subjects with bipolar disorder, eg, executive functions, working memory, attention, processing speed, and memory.…”
mentioning
confidence: 99%
“…The main difference was the presence of an epoxy group linked at C-5/6, on the basis of NMR signals at : 3.16 (brs, H-6), 61.20 (C-6) and 64.51 (C-5) and confirmed by HMBC analysis. Compound 2 was established as 5b, 6b-epoxy-4b,17a,27-trihydroxy-1-oxowitha-2,24-dienolide, a withanolide previously isolated from W. somnifera and W. aristata (Choudhary et al, 2004;Llanos et al, 2012), but reported here for the first time in W. frutescens.…”
Section: Chemistrymentioning
confidence: 72%